Pde4 mediates MHCII expression in oligodendroglia - Miguel M. Madeira; Zachary Hage; Dimitris Koliatsis; Alexandros G. Kokkosis; Kimberly Nnah; Alexander J. Rhee; Gilbert J. Rahme; Katherine Kamvisios; Antonis E. Koromilas; Barbara Rosati; David McKinnon; Stella E. Tsirka (Proceedings of the National Academy of Sciences, 2026)
Chronic psychosocial stress is a major precipitant of Major Depressive Disorder (MDD), yet the glial mechanisms that translate sustained stress into maladaptive myelin and immune changes remain unclear. Using chronic social defeat stress and single-nucleus RNA sequencing of anterior medial PFC (mPFC) oligodendroglia, we identified a mature-oligodendrocyte cluster almost exclusively from stress-susceptible animals, marked by immune genes (MHCII) and upregulated Pde4b. Integration with a human MDD single-nucleus RNA sequencing dataset confirmed a conserved immune-like oligodendrocyte (ImOL) subset coexpressing Plp1 and Cd74 and enriched for Pde4b. Mechanistically, PDE4 inhibition with crisaborole elevated cAMP–PKA–CREB signaling, blocked IFNγ-induced MHCII expression, and engaged the eIF2α–ATF4/CHOP arm of the integrated stress response (ISR). In vivo modulation of the ISR with ISRIB or guanabenz bidirectionally controlled ImOL prevalence and stress-related behaviors. These findings position Pde4b–cAMP–ISR signaling as a regulator of oligodendroglial immune phenotypes and a promising target to modulate myelination and neuroinflammation in stress-related disorders.